2008
DOI: 10.1161/hypertensionaha.107.106963
|View full text |Cite
|
Sign up to set email alerts
|

Liver X Receptor Activator Downregulates Angiotensin II Type 1 Receptor Expression Through Dephosphorylation of Sp1

Abstract: Abstract-Atherosclerosis is considered to be a combined disorder of lipid metabolism and chronic inflammation. Recent studies have reported that liver X receptors (LXRs) are involved in lipid metabolism and inflammation and that LXR agonists inhibit atherogenesis. In contrast, angiotensin II is well known to accelerate atherogenesis through activation of the angiotensin II type 1 receptor (AT1R). To better understand the mechanism of LXR on the prevention of atherogenesis, we examined whether activation of LXR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
1
15
1
1
Order By: Relevance
“…The transcriptional regulation of ACE is largely unknown, whereas regulation of AT 1 R is tight, complex and well described. 14 Our findings of decreased renal AT 1 R mRNA expression are in line with those of Imayama et al, 15 who demonstrated LXR to be a negative regulator of AT 1 R in cultured vascular smooth muscle cells. On the other hand, Leik et al showed that LXR activation by GW3965 leads to a transient increase in vascular gene expression of the AT 1 R, which decreased over time (measured over an 8-h period).…”
Section: Lxr-a and The Raas I Kuipers Et Alsupporting
confidence: 89%
“…The transcriptional regulation of ACE is largely unknown, whereas regulation of AT 1 R is tight, complex and well described. 14 Our findings of decreased renal AT 1 R mRNA expression are in line with those of Imayama et al, 15 who demonstrated LXR to be a negative regulator of AT 1 R in cultured vascular smooth muscle cells. On the other hand, Leik et al showed that LXR activation by GW3965 leads to a transient increase in vascular gene expression of the AT 1 R, which decreased over time (measured over an 8-h period).…”
Section: Lxr-a and The Raas I Kuipers Et Alsupporting
confidence: 89%
“…Thus, we assume that the TLR-4 pathway may not be involved in LXR-mediated inflammatory pathways. In addition, although AT1 is inhibited by LXR activation in smooth muscle 31 , we did not observe any significant difference in AT1 expression in PAH cardiocytes. Similar results were noted in our previous in vitro experiment.…”
Section: Discussioncontrasting
confidence: 75%
“…For instance, activation of PPARg by rosiglitazone has been shown to decrease AIIinduced SMC hypertrophy (Benkirane et al, 2006). In contrast, PPARd agonists decrease SMC senescence associated with AII (Kim et al, 2011), and LXR agonists decrease expression of the AT 1 R receptor (Imayama et al, 2008). The effects of rexinoids on SMCs have not been studied; however, in endothelial cells, bexarotene inhibits tumor necrosis factor a-induced adhesion molecule expression and decreases mononuclear cell recruitment (Sanz et al, 2012).…”
Section: Orgmentioning
confidence: 99%